GAMBARAN PEMERIKSAAN KADAR GLUKOSA DAN KOLESTEROL PADA LANSIA - Nur Vita Purwaningsih; Fitrotin Azizah; Ellies Tunjung Sari Maulidiyanti; Dita Artanti (Universitas Muhammadiyah Surabaya, 2019)
The increasing life expectancy based on WHO indicates an increase in the number of elderly people (elderly) so that there is an increase in health problems in the elderly due to the aging process which causes many changes in the body of the elderly. One of the changes in the body of the elderly is the blood glucose and cholesterol regulation system, resulting in an increase of more than normal. The purpose of this study was to determine the profile of glucose and cholesterol levels in the elderly. This research is observational. The population and sample in this study were the elderly in Karang Penang. The examination method used in this examination is the POCT (Point Of Care Test) examination method. The results showed that the elderly who had levels as much as 10 respondents (20%) samples had normal glucose levels, while as many as 40 respondents (80%) samples had high glucose. For cholesterol levels, 20 respondents (40%) samples had normal cholesterol levels, while 13 respondents (26%) samples had threshold cholesterol levels, then 7 respondents (14%) samples had high cholesterol levels. Keywords : blood glucose, cholesterol and the elderly